Effect of Nitrogen Starvation on Desiccation Tolerance of Arctic Microcoleus Strains (Cyanobacteria) - Daria eTashyreva; Josef eElster (Frontiers in Microbiology, 2015)
Although desiccation tolerance of Microcoleus species is a well-known phenomenon, there is very little information about their limits of desiccation tolerance in terms of cellular water content, the survival rate of their cells, and the environmental factors inducing their resistance to drying. We have discovered that three Microcoleus strains, isolated from terrestrial habitats of the High Arctic, survived extensive dehydration (to 0.23 g water g-1 dry mass), but did not tolerate complete desiccation (to 0.03 g water g-1 dry mass) regardless of pre-desiccation treatments. However, these treatments were critical for the survival of incomplete desiccation: cultures grown under optimal conditions failed to survive even incomplete desiccation; a low temperature enabled only 0 to 15% of cells to survive, while 39.8 to 65.9% of cells remained alive and intact after nitrogen starvation. Unlike Nostoc, which co-exists with Microcoleus in Arctic terrestrial habitats, Microcoleus strains are not truly anhydrobiotic and do not possess constitutive desiccation tolerance. Instead, it seems that the survival strategy of Microcoleus in periodically dry habitats involves avoidance of complete desiccation, but tolerance to milder desiccation stress, which is induced by suboptimal conditions (e.g. nitrogen starvation).